Lesion Studies in Contemporary Neuroscience. Issue 8 (August 2019) - Vaidya, Avinash R.; Pujara, Maia S.; Petrides, Michael; Murray, Elisabeth A.; Fellows, Lesley K.
Abstract : Studies of humans with focal brain damage and non-human animals with experimentally induced brain lesions have provided pivotal insights into the neural basis of behavior. As the repertoire of neural manipulation and recording techniques expands, the utility of studying permanent brain lesions bears re-examination. Studies on the effects of permanent lesions provide vital data about brain function that are distinct from those of reversible manipulations. Focusing on work carried out in humans and nonhuman primates, we address the inferential strengths and limitations of lesion studies, recent methodological developments, the integration of this approach with other methods, and the clinical and ecological relevance of this research. We argue that lesion studies are essential to the rigorous assessment of neuroscience theories. Highlights: Lesion studies have been fundamental to many core theories in cognitive and behavioral neuroscience. Lesion work in human and nonhuman primate lesion studies has unique inferential strengths that are distinct from temporary manipulations or correlative measures of neural activity. New methodological developments are underway that are expanding the range of questions that can be tested in studies of subjects with brain lesions. Lesion studies form a crucial bridge between basic science and behavior in the clinic and real-world settings. Testing theories with multiple lines of evidence using different approaches, including lesion studies, manipulations of neural activity, and correlations with neural activity, will be essential to the future of neuroscience.